Spectral characterization and surface morphology of delignification of Kraft pulp with carbamide peroxide. Issue 5 (October 2018) - Menon, Akshay; Akhil, T.; Krishna Prasad, R.
Highlights: Process model is developed for interactions of consistency of pulp, temperature and dosage of carbamide peroxide on Kappa number. Spectral analysis of pulp bleaching with carbamide peroxide is done using FTIR, XRD and FT-Raman spectroscopy. Abstract: The study focuses on delignification of Kraft pulp using carbamide peroxide as bleaching agent. The Kappa number reduction of bleached pulp is favored at low consistency of pulp and higher reaction temperature. The optimal Kappa reduction was achieved at temperature of 68 °C, 0.8 g of carbamide peroxide per 100 ml of solution and 2% consistency in the range of variables studied. Fourier transform infrared spectral analysis done on bleached pulp to determine bond stretches and bending vibrations. X ray diffraction spectral data observation provided that the crystallinity index increased from 81.7% before bleaching to 85% after bleaching which indicates the removal of amorphous species in sample. FT-RAMAN spectral analysis concludes the possible conformational changes pre and post bleaching. The absence of some native lignin bands post bleaching indicates lignin removal. Scanning electron microscope images of bleached pulp samples were observed with less amounts of fibrillar type lignin network on surface of pulp fibers when compared to unbleached samples. The activation energy and rate constants were determined for delignification of pulp using carbamide peroxide process. Sequential treatment of Kraft pulp with carbamide peroxide and sodium percarbonate were also evaluated.